Adverse Drug Events caused by Serious Medication Administration Errors - Sawarkar, Abhivyakti (BMJ Qual Saf, 2012)
OBJECTIVE: To determine how often serious or life-threatening medication administration errors with the potential to cause patient harm (or potential adverse drug events) result in actual patient harm (or adverse drug events (ADEs)) in the hospital setting. DESIGN: Retrospective chart review of clinical events that transpired following observed medication administration errors. BACKGROUND: Medication errors are common at the medication administration stage for hospitalized patients. While many of these errors are considered capable of causing patient harm, it is not clear how often patients are actually harmed by these errors. METHODS: In a previous study where 14,041 medication administrations in an acute-care hospital were directly observed, investigators discovered 1271 medication administration errors, of which 133 had the potential to cause serious or life-threatening harm to patients and were considered serious or life-threatening potential ADEs. In the current study, clinical reviewers conducted detailed chart reviews of cases where a serious or life-threatening potential ADE occurred to determine if an actual ADE developed following the potential ADE. Reviewers further assessed the severity of the ADE and attribution to the administration error. RESULTS: Ten (7.5% [95% C.I. 6.98, 8.01]) actual adverse drug events or ADEs resulted from the 133 serious and life-threatening potential ADEs, of which 6 resulted in significant, three in serious, and one life threatening injury. Therefore 4 (3% [95% C.I. 2.12, 3.6]) serious and life threatening potential ADEs led to serious or life threatening ADEs. Half of the ten actual ADEs were caused by dosage or monitoring errors for anti-hypertensives. The life threatening ADE was caused by an error that was both a transcription and a timing error. CONCLUSION: Potential ADEs at the medication administration stage can cause serious patient harm. Given previous estimates of serious or life-threatening potential ADE of 1.33 per 100 medication doses administered, in a hospital where 6 million doses are administered per year, about 4000 preventable ADEs would be attributable to medication administration errors annually.